PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MOBIL MITSUBISHI PADA PT. KRAMA YUDHA MOTORS AND MANFACTURING - Dwi Ardika Prayudha; Nuridin (Jurnal Manajemen Bisnis Krisnadwipayana, 2018)
This research is aimed to examine the influence of brand image and product quality to car purchase decision at PT. Mitsubishi Krama Yudha Motors and Manufacturing. Data analysis method was used, is quantitative analysis, by using validity and reliability test, coefficient of determination, and multiple linear regression analysis. Result of regression equation is: Y = 0,665 + 0,517 X1 + 0,416 X2 Simultaneously testing of brand image variables and product quality to purchase decision, shown by F count equal to 85,955 bigger than F table 3,159 or with sig. F 0.000 is smaller than alpha 0.005. Based on the test results simultaneously, can be seen that the independent variables (brand image and product quality) have a positive and significant impact on the car purchase decision at Mitsubishi cars At PT. Krama Yudha Motors and Manufacturing. Suggestions which can be given for future developments and determinations of policy are, companies should pay attention to brand image, product quality, to make customers more satisfied and keep using Mitsubishi cars as their choice.